Assessment of a New Type I Endoleak Repair Technique Using an Anchoring Device. Issue 4 (June 2013) - Tuan, Pham Minh; Ohtake, Hiroshi; Ryuta, Seguchi; Watanabe, Go
Objective: Type I endoleaks are one of the most frequent and life-threatening complications of thoracic endovascular aortic repair. This study aimed to assess the use of suture-anchoring devices for repairing type I endoleaks. Methods: The descending aortic aneurysm model (saccular type) was made by side-to-end anastomosis to a Dacron graft. A Matsui-Kitamura stent graft was deployed to create a proximal type I endoleak. Approximately 5 mm above the upper rim of the anastomosis, the aorta was punctured by the pistol of the suture-anchoring device with a T-shaped bar under fluoroscopy. Sutures were applied until angiography showed the absence of a type I endoleak. During the process, two pressure measurements were used to perform continuous assessments of aortic pressure and intra-aneurysm sac pressure. Results: A mean ± SD of 5 ± 1 anchoring shots were used to eliminate type I endoleaks. The device performed well, and no complications were observed. The mean ± SD intrasac pressures before stent graft deployment, during endoleak maintenance, and after repair were 118 ± 5, 61 ± 4, and 26 ± 5 mm Hg, respectively. The postrepair pressure was significantly decreased ( P < 0.001; Student t test). Conclusions: Despite some anatomic and clinical limitations identified during the experiments, the effectiveness of the suture-anchoring device was confirmed. Further improvement of the device will soon lead to its use as a less invasive endoleak repair procedure.